Implementation of taipa de pilão as an alternative construction system, as to its environmental impact (Research, Society and Development, 2022)
This work evaluated the potential environmental effects of the rammed earth construction technique, taking into account several configurations typically found in Brazil. Three Portland cement contents were evaluated: 5%, 10% and 15%. (in large scale). The phases of production and transport of materials, construction and completion of Taipa's life cycle were considered through the Life Cycle Assessment (LCA) methodology. The various configurations of the rammed earth systems were contrasted with a masonry of structural ceramic blocks, structural concrete blocks and locally cast concrete walls. The calculated indices showed that the rammed earth is more advantageous, especially when the thermal capacity and the calculated sound reduction index are taken into account when choosing the functional unit. taipam were cement production and wood type. Therefore, it was possible to determine the potential life cycle environmental effects of this construction technique, which were parameterized by wall and cement thickness, with regression-derived equations being presented. Recommendations were also made to improve the environmental impact of rammed earth amid current environmental problems.